Electric Power Deficit and Economic Growth in Nigeria: A Sectoral Analysis - Henry, James Tumba; Ndem, Bassey Enya; Ujong, Ofem Lekam; Ihuoma, Chijioke Mercy (International Journal of Energy Economics and Policy, 2021)
In addition to capital and labour, electricity supply is another important factor that promotes economic growth in an economy. Often times, economic resources are used to generate electricity for domestic consumption by different sectors of an economy. In Nigeria however, the generated KWh is far higher than what eventually gets to the final consumers due to technical inefficiencies associated with electric power transmission and distribution in the supply chain resulting in huge losses. Thus, this study investigated the effect of electric power deficit proxied by electric power transmission and distribution losses on economic growth (disaggregated into agricultural and industrial RGDP) in Nigeria. This study employed the Autoregressive Distributed Lag (ARDL) model and time series data from 1981 to 2017. The hypotheses tested in this study were done at 5 and 10 percent levels of significance. The result obtain revealed that a 1 percent increase in electric power transmission and distribution losses will decrease agricultural output by 3 percent in the long run but insignificant in the short run. Similarly, electric power transmission and distribution losses do not have significant effect on industrial output. It was therefore recommended that the government should construct energy farms to muster and store the electricity that is produced before they are transmitted to the final consumers. Keywords: technical inefficiencies, electric power deficit, economic growth, energy farms JEL Classifications: C12, C13, C30, F43, L70, Q19, Q43 DOI: https://doi.org/10.32479/ijeep.11491